Effects of postovulatory copulation among alpacas Huacaya (Vicugna pacos) on the embryonic survival rate - Ramos Rivas, Carla Fabiola (2020)
The study was carried out at the La Raya Experimental Center of the National University of the Altiplano of Puno at an altitude of 4200m,with the aim of evaluating the effect of additional post-ovulation copulations on embryonic survival. Huacaya alpacas were used withpostpartum sexual rest greater than 20 days, with a preovulatory follicle greater than 7 mm, verified by ultrasound. For the controlledmating, 5 males from the breeding group were used. After breeding, 26 to 35 hours post-mating, ovulation was verified, selecting 47alpacas that ovulated, and distributed to the experimental groups: G1 (n = 16) with no additional mating, G2 (n = 15) received anadditional mating 24 hours post-ovulation, and G3 (n = 16) two additional mating 48 hours post-ovulation. On days 14 and 24 aftercopulation, the presence of the corpus luteum and embryonic vesicle was verified by ultrasound and receptivity of the female to the male.Results show a higher percentage of embryo survival trend in alpacas that received additional mating at 24 and 48 h post-ovulation thanthose that received only one ovulatory mating, showing at 14 days post-copulation an embryonic survival of 93.3% and 87.5%, in G2and G3 respectively, compared to G1 with 75%, and at 24 days post-copulation 86.7% and 87.5% in G2 and G3 respectively, comparedto G1 (62,5%). Although no significant differences were observed between groups (P>0.05), the difference is observed in the simplecorrespondence analysis between groups.